Аналіз основних понять та визначень надійності систем авіоніки - Григор’єва, О. В.; Кожевникова, В. Г. (ХНУРЕ, 2025)
The work deals with the basic concepts and definitions related to the reliability of avionics systems. The key reliability properties, such as fault tolerance, durability, maintainability and safety, are described. The classification of products based on their ability to restore performance, as well as the types of connections of elements in systems are considered. The causes and types of failures, including sudden and gradual, are analyzed. The main factors affecting the reliability of avionics systems are presented.
Keywords: авіоніка; avionics systems